2020
DOI: 10.18865/ed.30.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Youth Enjoy Science Program at the Case Comprehensive Cancer Center: Increasing Engagement and Opportunity for Underrepresented Minority Students

Abstract: The Youth Enjoy Science (YES) Program at the Case Comprehensive Cancer Center is a National Cancer Institute (NCI) R25- funded training grant, designed to increase the pipeline of underrepresented minor­ity (URM) students entering college and pursuing biomedical research and health care careers in the Cleveland Metropolitan and surrounding school districts. The three components of the program include: Learn to Beat Cancer, engaging middle school students and their families; Research to Beat Cancer, designed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Descriptions of the overall SEO/ YES program and the near peer mentor component have previously been described. (Qua et al, 2020a;Qua et al, 2020b) In response to the pandemic, the program was adapted to a totally virtual format, using zoom technology. To design the new virtual format, we relied primarily on our previous 17-year experience with high school students, indicating that our most successful and well-received programs were those that were highly engaging and interactive, that involved active versus passive learning, that stimulated student question and answers and that encouraged students to think and interact on-the-spot.…”
Section: Introductionmentioning
confidence: 99%
“…Descriptions of the overall SEO/ YES program and the near peer mentor component have previously been described. (Qua et al, 2020a;Qua et al, 2020b) In response to the pandemic, the program was adapted to a totally virtual format, using zoom technology. To design the new virtual format, we relied primarily on our previous 17-year experience with high school students, indicating that our most successful and well-received programs were those that were highly engaging and interactive, that involved active versus passive learning, that stimulated student question and answers and that encouraged students to think and interact on-the-spot.…”
Section: Introductionmentioning
confidence: 99%
“…12 Innovation of a three-pronged program illustrates components reaching middle school students and their families, high school students and undergraduates, and high school teachers to strengthen capacity (Qua et al). 13 Of the 900 students enrolled in the SLAM high school program, 90% enrolled in college (Harris et al). 14…”
Section: K-12mentioning
confidence: 99%
“…Programs funded by the NCI and other cancer research training programs have been shown to increase awareness of cancer and cancer prevention methods (Cameron et al, 2012); increase interest in cancer research (Hein & Kidd, 2018); increase interest in medical and/or cancer-related careers (Alfred et al, 2011); and produce a high number of students pursuing and completing medical, professional, and doctoral programs (Alfred et al, 2011;Gronemeyer, 2011;Hein & Kidd, 2018). These programs for high school and undergraduate students have primarily focused on promoting cancer research training to underrepresented racial minority youth populations and/or students from urban areas (Alfred et al, 2011;Hein & Kidd, 2018;Qua et al, 2020).…”
Section: Introductionmentioning
confidence: 99%